Diagnostic Accuracy of Magnetic Resonance Imaging in Detecting Clear Renal Cell Carcinoma, Taking Histopathology as Gold Standard - Ammara Arshad, Nadia Irshad, Anam Ibrahim, Sumaira Yousaf, Sana Noor, Zahra Nasrullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Presurgical staging and characterization of renal masses can be accomplished with magnetic resonance imaging (MRI). Objective: Present study aims to determine the diagnostic accuracy of magnetic resonance imaging in detecting clear renal cell carcinoma, taking histopathology as gold standard. Study design: Descriptive, cross-sectional study. Study duration and settings: Study was conducted at department of Diagnostic Radiology, Jinnah Hospital, Lahore from 4th June 2018 to 3rd December 2018. Material and methods: A total of 133 patients with clear renal cell carcinoma on ultrasonography having age 20-60 years of either genders were enrolled. Patients with pregnancy, previous nephrectomy and contraindicated for MR studies were excluded. MRI abdomen was performed in every patient using the 1.5 Tesla MR system with gradient strength of 33mT/m. MRI findings were correlated with histopathology findings. Results: MRI of abdomen pelvis was performed in all patients and there were 68 True Positive and six False Positive results observed . Among 59 patients whose MRI was negative, 06 patients (False Negative) found clear renal cell carcinoma on histopathology, but True Negative patients had no clear RCC (p=0.0001).Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of diagnostic accuracy of magnetic resonance imaging in detecting clear renal cell carcinoma was 91.89%, 89.83%, 91.89%, 89.83% and 90.98% respectively Conclusion: This study concluded that magnetic resonance imaging is a highly sensitive and accurate non-invasive modality for diagnosing clear cell renal cell carcinoma.. Keywords: Renal cell carcinoma, magnetic resonance imaging, sensitivity